Prevalence, Incidence, and Associated Factors of Possible Sarcopenia in Community-Dwelling Chinese Older Adults: A Population-Based Longitudinal Study - Chen, Zi; Ho, Mandy; Chau, Pui Hing (Frontiers in Medicine, 2022)
Purpose: This study aimed to assess the prevalence, incidence, and associated factors of possible sarcopenia in a nationwide representative sample of the community-dwelling older Chinese population. Methods:This study used the data of participants aged 60 years and over from the China Health and Retirement Longitudinal Study (CHARLS). Data on participants from three waves (2011–2015) of CHARLS were extracted. Possible sarcopenia was defined as low muscle strength or low physical performance, based on the Asian Working Group for Sarcopenia 2019 consensus. We first described baseline prevalence and four-year incidence of possible sarcopenia. Then multiple logistic regression and multivariable parametric proportional hazard model with Weibull distribution were used to examine the association of risk factors with baseline prevalence and four-year incidence of possible sarcopenia, respectively. Results:The prevalence of possible sarcopenia was 46.0%. The four-year incidence of possible sarcopenia was 11.9 per 100 person-years. Multivariable analysis revealed that advanced age and depressive symptoms were associated with increased prevalence of possible sarcopenia, while receiving education and moderate or high physical activity were associated with a lower risk of possible sarcopenia prevalence. For incidence, only advanced age was associated with an increased risk of possible sarcopenia incidence. Conclusion:Our study revealed the substantial burden of possible sarcopenia and related risk factors in community-dwelling settings in China. It highlighted the importance of early detection and intervention in this subclinical group for the prevention of sarcopenia.